BERBAGAI BENTUK PEMANFAATAN BANGUNAN INDIS DI KOTA MALANG: PEMIKIRAN AWAL TENTANG PENGELOLAAN BCB - Chawari, Muhammad (Berkala Arkeologi, 2010)
The use of archaeological resources (BCB) in Indonesia is regulated in Law No. 5 1992 on Cultural Property and Indonesian Government Regulation No. 10 1993 on the implementation of the Law no. 5 1992. According to these regulations, cultural property may be used for many purposes such as religious, social, tourism, education, science, and cultural purposes. This paper illustrates the use of some colonial buildings in the City of Malang which is not only in accord with the regulations but also added economical value. the building could also be associated with economical value. There are some examples in Malang showing the use of BCB based on its economical value, but the implementation tended to be individualistic and hasn't reached international level yet. The practical activities include: Festival Malang or Malang Old Festival; producing t-shirts and sticker with pictures of indis buildings; displaying pictures of indis buildings in restaurants, hotels, and stores, and also making various forms of old advertisement by one of the bakery in Malang.